PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V11B SMPN 2 SINABOI TAHUN PELAJARAN 2015/2016 - Wira Wahyu; Sri Wulandari; Suwondo ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to improve science learning outcomes of students with the application of cooperative learning model Numbered Heads Together at SMPN 2 Sinaboi VIIB class in the academic year 2015/2016. Which was conducted in March 2016. The subjects were students of SMPN 2 Sinaboi VIIB grade school year 2015/2016 with a total of 25 people (11 students and 14 female students). Which lasted for two cycles in which the first cycle with the material classify living things based on the characteristics possessed by the material and the second cycle describes the diversity of the organizational system of life from the cellular level up to 3 times the organism replicates harian. Parameter meetings including that measured learning outcomes students consisting of absorption students and students learning completeness, awards groups, student activities and teacher's activities. Absorptive capacity of the students in the first cycle 73% (enough) and the second cycle 82.4% (good). Mastery learning in the first cycle 80% complete and has increased in the second cycle at 88%. Group awards in the first cycle there is one super group and the second cycle there are two super groups. Average student activity in cycle I 60.38% (or less) and the second cycle increased to 86% (excellent). The average teacher activity increased by 90.5% (excellent) and the second cycle of 100% (excellent). From these results it can be concluded that cooperative learning model NHT can improve learning outcomes IPA class VII SMPN 2 Sinaboi in the academic year 2015/2016.Keywords: Learning Outcomes IPA, Cooperative Learning, Kooperati Type Numbered Heads Together (NHT)